Soil cadmium mobilisation by dissolved organic matter from soil amendments. (May 2021) - Welikala, Dharshika; Robinson, Brett H.; Moltchanova, Elena; Hartland, Adam; Lehto, Niklas J.
Abstract: Dissolved organic matter (DOM) release from Cd contaminated soils been linked to mobilisation of the metal as Cd-DOM complexes and this may be exacerbated by organic matter-rich soil amendments. The quantity and quality of the DOM can determine the proportion of dissolved Cd that partitions to mobile complexes and their stability and, thus, the potential for Cd transport from contaminated soils. The aim of this work was to examine differences in Cd mobilisation from soils to which different types of soil amendments/conditioners have been applied and the importance of DOM characteristics in determining the extent to which this can happen. Three soils were spiked with Cd to 2 mg kg −1, allowed to equilibrate and then treated with compost and peat. These soils and an untreated subsample of each soil were then adjusted to three different pHs: 5.6, 6.4 and 7.4, using lime. The amount of Cd mobilised from each soil was tested using a column leaching experiment. Ultrafiltration and speciation modelling were used to determine amounts of Cd as DOM-complexed, "truly" dissolved (<5 kDa) and colloidal species, while DOM quality was assessed using UV–Vis and fluorescence spectroscopy. Most colloidal Cd was mobilised from the compost treated soils (50%–60%), followed by the peat treated soils (20–44%). The relationships between colloidal Cd, DOC concentration and soil pH, together with the spectroscopic and modelling results showed that structural properties of DOM are an important factor in mobilising Cd from contaminated soils. Highlights: Cd mobilisation from soils treated with organic matter-rich substrates was tested. Mobilisation was reduced by the treatments at soil pH 5.6 and by liming to 7.4 Treating soils with compost and peat at pH 6.4 increased Cd mobilisation. Dissolved organic matter quality can determine extent of Cd mobilisation.